Tanggung Jawab Negara Terhadap Lingkungan Hidup yang Baik dan Sehat Berdasarkan Prespektif Hak Asasi Manusia - Maya Lorenza; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The diminishing quality of the environment has threatened the survival of human life and other living things. Therefore, it is necessary to do the protection and management of the environment that is truly and consistently by all stakeholders. Forest and land fires in Sumatra, such as Riau, Jambi, South Sumatra and parts of Borneo, have caused smog in at least the last three months of 2015. State power is concerned with responsibilities and obligations. Viewed from the aspect of the development of democracy, these two things are elements of the unity of the notion of power. Today there is hardly a power that is not followed by responsibility and obligation. For if not, that would lead to a totalitarian state. Based on this understanding, the authors formulate two formulation of the problem, namely: First, What is the responsibility of the State against forest burning and lahandalam human rights perspective? Second, what are the regulations issued by the Government related to the burning of forests and land?Research methods in this research, First, the type of research is normative law and descriptive analysis. Second, data sources are supported by primary data sources, secondary data, and tertiary data. Third, the data collection technique used is literature study. After the data collected then analyzed qualitatively, and draw conclusions with the deductive thinking method of analyzing the problem from the general shape to the special form.From the results of research problems there are two main things that can be concluded. Firstly, Indonesia in its responsibility as a State of law must provide protection for basic rights, especially the rights of the community on a good and healthy environment, in fact in its implementation has not been done by the state with the maximum. It can cause the Indonesian state to suffer huge losses to forest and land burning to some neighboring countries in particular that would have an impact that not only disrupts the surrounding country's ecosystem but also affects business activities in real sectors such as tourism and air transportation. Secondly, in the framework of regulations issued by the Government related to the burning of forests and land, the State of Indonesia has at least four legal ranks, namely the Constitution of the Republic of Indonesia Year 1995, Law of the Republic of Indonesia Number 18 Year 2013 on Prevention and Eradication of Forest Destruction, -Undonesia Republic of Indonesia Number 39 Year 1999 on Human Rights, and Law of the Republic of Indonesia Number 32 Year 2009 on Environmental Protection and Management. Such law enforcement through the approach of criminal law, international law, and constitutional law actually provides an alternative to uphold justice. But it seems the four laws are seen not to give an answer to the sense of justice.Keywords: State Responsibility - Environment - Human Rights